Story-Telling Ballads : Selected and Arranged for Story-Telling and Reading Aloud and for the Boys' and Girls' Own Reading - Olcott, Frances Jenkins, 1872-1963; Winter, Milo, 1888-1956 (Salt Lake City, UT : Project Gutenberg, 2020)
"Story-Telling Ballads" by Frances Jenkins Olcott is a collection of ballads and narrative poems curated for young readers, written in the early 20th century. This compilation features 77 ballads, drawing from traditional lore, legends, and adventures from various cultures, tailored for children aged twelve to fifteen. The chosen selections aim to capture the imagination of youthful audiences with stirring tales of heroism, magic, and romance. At the start of the text, readers are introduced to the purpose of the collection and the nature of the ballads included. The foreword discusses how ballads historically served as a mode of storytelling that enthralls young listeners with themes of chivalry, love, and adventure. Additionally, it emphasizes the importance of these narratives in both entertaining children and imparting life lessons. The opening highlights the rich diversity of characters and stories awaiting the reader, as well as the significance of ballads in nurturing a love for literature and learning. (This is an automatically generated summary.)
Release date is 2020-11-23
E-text prepared by MFR, Susan Carr, and the Online Distributed Proofreading Team (https://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Children's poetry, English; Recitations; Children's poetry, American; English poetry -- Collections; Ballads, English -- England -- Texts; American poetry -- Collections; Ballads, Scots -- Scotland -- Texts; Narrative poetry, American; Narrative poetry, English